2002
DOI: 10.1093/embo-reports/kvf002
|View full text |Cite
|
Sign up to set email alerts
|

Wnt signals are transmitted through N‐terminally dephosphorylated β‐catenin

Abstract: β-catenin mediates Wnt signaling by acting as the essential co-activator for TCF transcription factors. Wnt signaling increases the half-life and therefore the absolute level of β-catenin in responding cells. The current model states that these changes in β-catenin stability set the threshold for Wnt signaling. However, we find that pharmacological inhibition of proteasome activity by ALLN leads to accumulation of cytosolic β-catenin but not to increased TCF-mediated transcription. In addition, in temperature-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
297
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(328 citation statements)
references
References 33 publications
28
297
3
Order By: Relevance
“…When a Wnt protein binds to the receptor complex consisting of a member of the Frizzled (Fz) family of seven transmembrane proteins 71 and an LDL-receptorrelated protein (LRP5 or LRP6), 72 b-catenin is no longer phosphorylated, resulting in its accumulation and activation. 73 Deposphorylated b-catenin translocates to the nucleus, where it activates Tcf/Lef transcription factors, 74,75 in thymocytes predominantly Tcf-1. 76,77 Next to the canonical Wnt-signaling pathway, b-catenin-independent mechanisms exist (reviewed by Veeman et al 78 ), but their implications for T-cell development have not been studied in detail.…”
Section: Wnt Signaling In the Thymusmentioning
confidence: 99%
“…When a Wnt protein binds to the receptor complex consisting of a member of the Frizzled (Fz) family of seven transmembrane proteins 71 and an LDL-receptorrelated protein (LRP5 or LRP6), 72 b-catenin is no longer phosphorylated, resulting in its accumulation and activation. 73 Deposphorylated b-catenin translocates to the nucleus, where it activates Tcf/Lef transcription factors, 74,75 in thymocytes predominantly Tcf-1. 76,77 Next to the canonical Wnt-signaling pathway, b-catenin-independent mechanisms exist (reviewed by Veeman et al 78 ), but their implications for T-cell development have not been studied in detail.…”
Section: Wnt Signaling In the Thymusmentioning
confidence: 99%
“…These studies indicated that Since cyclin D1 is a direct target of the b-catenin/ lymphoid enhancer factor (LEF)-mediated pathway (Tetsu and McCormick, 1999), we determined whether G-17 could induce cyclin D1 transcription, via the activation of the Wnt-signaling pathway. To address this, we first determined the effect of G-17 on b-catenin expression, by Western blot analysis of AGSE wholecell protein extracts, treated without (À) or with ( þ ) 100 nM G-17, using antibodies specific to total b-catenin, as well as N-terminally dephosphorylated/activated bcatenin (ABC b-catenin), as reported previously (Staal et al, 2002). The results indicated significant induction of dephosphorylated/activated b-catenin (Figure 3c, À and þ lanes) and minor induction of total b-catenin (Figures 3a and b) following G-17 stimulation, which was associated with an increase in b-catenin nuclear translocation (Figure 3d, compare V panel with G-17 panel).…”
Section: G-17 Induces Cyclin D1 Transcription and Activates The Wnt-smentioning
confidence: 99%
“…The sections were rinsed in PBS and non-specific binding of antibodies was blocked with serum for 30 min at room temperature, before application of the primary antibody. Primary antibodies used in this study were: anti-b-catenin (reacting with total human and mouse b-catenin, BD Biosciences), aABC-b-catenin (reacting with nonphosphorylated Ser-37 and Thr-41, the active forms of b-catenin; Staal et al, 2002;van Noort et al, 2002;clone 8E7, Millipore), anti-ZO-1 (clone 61-7300, Life Technologies) and anti-actin (clone C4, Millipore). For controls, the primary antibody was omitted to verify expression patterns (data not shown).…”
Section: Methodsmentioning
confidence: 99%
“…This monoclonal antibody reacts against nonphosphorylated forms of b-catenin, which are active within the canonical Wnt signalling pathway (Staal et al, 2002;van Noort et al, 2002). Non-phospho-b-catenin detection showed a membranous, suprabasal expression pattern in control as well as HPV8-E7 positive OSC.…”
Section: Hpv8-e7 Mediates Overexpression Of B-catenin In Oscmentioning
confidence: 99%